What Is the Relationship between Lifestyle and Frailty Status? Data from the Portuguese Multicentre Descriptive Study - Luísa Teixeira-Santos; Elzbieta Bobrowicz-Campos; Vitor Parola; Adriana Coelho; Isabel Gil; Maria de Lurdes Almeida; João Luís Apóstolo (MDPI AG, 2022)
This observational and descriptive study attempted, within the scope of the ModulEn Research Project, to determine associations between lifestyle-related variables and frailty involving 160 community-dwelling older adults aged between 65 and 80 years living in the Central Region of Portugal. Forty-three percent of the study participants were pre-frail and 18% were frail. More than 50% of the frail people had slight cognitive decline, and the frailty condition was more frequently observed in women. As the literature highlights, there is potential for greater reversibility in the pre-frailty condition. To contribute to this reversibility, it is necessary to resort to interventions that promote physical activity and cognitive stimulation, apply adequate eating habits, and/or encourage the adoption of an active and socially integrated lifestyle. A healthy lifestyle implies good sleep and eating habits, and correct metabolic control that allows for effective surveillance of dyslipidemia, diabetes, and blood pressure.